PENGEMBANGAN E-MODUL MATEMATIKA DENGAN CANVA TERINTEGRASI NILAI KEISLAMAN - Triani, Elis; Prabawati, Mega Nur; Kurniawan, Dian (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
This study aims to explore the development process of a mathematics e-module integrated with Islamic values using Canva. The research employs a research and development (R&D) approach. The research design follows the ADDIE model, which comprises five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The data analysis technique utilized in this study is quantitative descriptive analysis.The development process begins with the analysis stage, which involves selecting the e-module as the instructional material based on problem identification and learning objectives to be included in the e-module. The design stage produces an e-module layout that includes an introduction, main content, and conclusion. Subsequently, the development stage encompasses the feasibility testing of the e-module through validation by subject matter experts in mathematics, Islamic studies, and media, all of whom rated it as "Highly Appropriate." A limited-scale trial also yielded "Highly Positive" responses from students. During the implementation stage, a broader scale trial was conducted, and the developed e-module received "Highly Positive" feedback from students, with a satisfaction rate of 89.02%. Lastly, the evaluation stage was carried out throughout the research process, from analysis to implementation. The outcome of this research is a Canva-developed e-module integrated with Islamic values.